The Imperative Need for Criminological Research on the European Roma: A Narrative Review. (April 2023) - Molnar, Lorena
Except for the knowledge that the Roma people endure harsh conditions and are victims of discrimination, scarce criminological research has given detailed attention to further victimisation or offending among the Romanies. Identifying articles in the browsers Web of Science, Google Scholar and Google, we reviewed European publications (1997–2020) in English, French, Romanian or Spanish that addressed the Roma's victimisation or offending. The 44 studies that matched our criteria suggested that (1) Roma people are victims of hate crimes with devastating consequences; (2) Roma children and women are victims of domestic violence to a greater degree than other groups, although the Roma tend to oppose violence against women; (3) forced early marriages exist among some Romanies and may cause serious problems in adulthood; (4) youth delinquency among the Roma does not differ from that of the non-Roma, although Roma adolescents face more deprivation; (5) Roma men and women are overrepresented in prison and face many difficulties in re-entering society once they are released and (6) there are organised criminal activities in some Roma groups that are supported by their community. Further rigorous post-positivist research, particularly quantitative, is needed to generalise the findings and replicate former studies. Areas of special interest are the causes of anti-Roma discrimination other than ethnicity, the victimisation of children, the Roma's lack of institutional trust and the relation between victimisation and offending. Conducting comparisons with the general population is essential, and we propose that victims' surveys and self-reported delinquency studies include questions on ethnicity.